ISOLATION OF A FLAVONOID FROM THE ROOTS OF CITRUS SINENSIS - JAVED INTEKHAB; MOHAMMAD ASLAM (Universiti Sains Malaysia, 2009)
Citrus sinensis is native to Asia and throughout the Pacific and warm areas of the world. The ethyl acetate extract of the roots of Citrus sinensis yielded a flavonoid. The compound was characterizedas 5, 8-dihydroxy-6, 7, 4'-trimethoxyflavone on the basis of UV, I.R, mass and N.M.R (1H, 13C) spectral studies. We believe this is the first report describing the isolation of flavonoid from thisplant.